How good is social equality in the Peninsular Malaysia; a cross-sectional study among bumiputera community / Mohd Nazir Rabun ... [et al.] - Rabun, Mohd Nazir; Mohamed Ali, Abdul Jalil; Abdullah, Nuraisyah Chua (Universiti Teknologi MARA, Kedah, 2022)
This study intends to explore and understand the views and livelihood of the Bumiputera communities in facing the ever challenging social, economic and political environments around them. It is necessary because the impact of post- New Economic Policy (1971-1990) for these communities should not be devastating. The NEP was the brainchild of our concern political masters in preparing specifically the Malays and Bumiputras to control the social, economic and political well being for many, many centuries to come. As a consequence, numerous affirmative policies were carried out by the government to reach the above dream. This study tries to determine the levels of social equality based on the seven (7) social indicators namely health, quality of life, housing, occupation, income, education, and participation among Bumiputera in the Peninsular Malaysia. Social equality among the Bumiputera community appears to be modetare when looking at overall. Findings also revealed that education found to be the perceived highest indicator by the majority of Bumiputera community.